REPORT ON A COLLECTION OF TONGUE SOLES iCYNOGLOSSUS SPP.) FROM MOPLAH BAY WITH A DESCRIPTION OF C. LIDA (BLEEKER) - Seshappa, G (Indian Journal of Fisheries, 2011)
A sample of 49 specimens of tongue soles (Cynoglossus spp.) was collectedon 14th February 1968 from the Moplah Bay, Cannanore*. Thesample was interesting in that as many as four species were represented in it,including also the common Malabar Sole, C. semifasciatus Day. The presentnote deals with the biological findings on this material (examined after preservationin formalin) together with certain morphological and ichthyolc^ical dataon the species other than C. semifasciatus. A description of C. lida (Bleeker)is also included as the species has not so far been described from this coast.The present author (Seshappa 1970) has made a morphometric study of C. lidain comparison with four other species from the west coast.